(untitled) (Damascus University Journal of arts and humanities sciences, 2021)
Tartous governorate is the leading producer of protected tomatoes and cucumber in Syria. It enjoys the geographical conditions that are suitable for the success this type of agriculture. The production of protected tomatoes and cucumber in Tartous governorate did not decrease despite the war on Syria. This fact was confirmed by the statistical significance test of the general trend line of production of the two crops in three periods (2002 - 2017), (2002 -2010) and (2011 – 2017). Concentration areas for protected cultivation of tomatoes and cucumber were determined on the level of administrative regions in Tartous governorate by calculating the concentration index. In addition, the coefficient of spatial specialization was calculated for the two crops. The study showed that there is a spatial concentration in the cultivation of tomatoes in most of the administrative regions of the governorate except in Safita and Drikish. Protected cucumber cultivation was concentrated in administrative area of central Tartous. The administrative areas of Banias and central Tartous were specialized in protected Tomatoes production, while central Tartous was specialized in cucumber production.